Compact Planar Antenna For Metal-Mountable Uhf RFID Tag Design - Tan, Philip Boon Hong (2020)
An electrical small planar folded patch composes of a rectangle Split-Ring Resonator (SRR) which is excited and fed by a meandered T-match, is proposed for designing an electrically small passive UHF RFID tag antenna for mounting on various dielectric constant dielectric surfaces. It has a dimension of 28 mm  28 mm  3.293 mm (0.0854λ × 0.0854λ × 0.01004λ). The tag antenna is able to generate stable omnidirectional read patterns when placed on dielectric material. The notches have been merged with an inductive stub for the purpose of tuning the tag’s resonance frequency. Good power transmission coefficient of ~90% is attainable. Measurements are conducted with reference to a transmitting power of 4W EIRP, and it has been shown that the proposed tag antenna is able to generate omnidirectional radiation patterns with a stable realized gain of -6.28 dB to -5.90 dB when it is placed on dielectrics with permittivity in the range of 1 – 5.8 in all directions in the azimuth plane. The tag’s resonant frequency is also very stable and it is not affected by the dielectric with different permittivity backing surface much as the resonant frequency varies only in the range between 910 MHz to 917 MHz when the permittivity changes.